Differential Subordinations for Certain Meromorphically Multivalent Functions Defined by Dziok-Srivastava Operator. (18th June 2011) - Yang, Ying; Tao, Yu-Qin; Liu, Jin-Lin
Abstract : By making use of the Dziok-Srivastava operator, we introduce a new class of meromorphically multivalent functions. Some inclusion properties of functions belonging to this class are derived.